Advanced human nutrition - Medeiros, Denis M.; Wildman, Robert E. C. 1964- (Jones & Bartlett Learning, 2015)
Written for the upper-level undergrad or graduate level majors course, Advanced Human Nutrition, Third Edition provides an in-depth overview of the human body and details why nutrients are important from a biochemical, physiological, and molecular perspective. Through its writing style and numerous figures and illustrations, the Third Edition clearly outlines metabolism and the molecular functions of nutrients. A variety of pedagogical elements within the text, such as "Here's Where You Have Been" and "Here's Where You Are Going," help clarify key points from the chapter and provide real-world examples that bring the content to life. New and Key Features of the Third Edition: • Includes new chapters on Fiber and Nutraceuricals and Functional Foods • "Before You Go On" sections asks students to reflect upon what they've just read, urging them to go back and re-read portions of the text if they do not readily grasp the material. • "Special Feature" boxes on focused topics add depth to the chapter and, in some cases, allow the student to view the application of basic science. • The end-of-chapter summary reiterates key points from the chapter and helps students prepare for future exams.